Leistung und Erfolg im modernen Leistungssport - Müller, A. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Quite often at major sporting events, such as the Rio de Janeiro 2016 Olympic Games, a confusion of performance with success can be noticed. This gets evident especially because of the focusing of national associations on medals only. This paper will address some of the aspects against a pure obsession with medals form a philosophical perspective.